2001
DOI: 10.1186/1471-2393-1-2
|View full text |Cite
|
Sign up to set email alerts
|

Manipulation of the follicular phase: Uterodomes and pregnancy - is there a correlation?

Abstract: Background: Manipulation of the follicular phase uterine epithelium in women undergoing infertility treatment, has not generally shown differing morphological effects on uterine epithelial characteristics using Scanning Electron Microscopy (SEM) and resultant pregnancy rates have remained suboptimal utilising these manipulations. The present study observed manipulation of the proliferative epithelium, with either 7 or 14 days of sequential oestrogen (E) therapy followed by progesterone (P) and assessed the app… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
18
0
1

Year Published

2003
2003
2013
2013

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 56 publications
(75 reference statements)
0
18
0
1
Order By: Relevance
“…Originally termed 'pinopods' from studies in rats which established a pinocytotic function for them in this species [43], large, rounded, smooth-surfaced projections of the apical plasma membrane have been identified in the uterine epithelium of many species during early pregnancy ranging from rabbits and rodents through camels to human beings [44,45]. Because such smooth-surfaced projections occur during the receptive phase for blastocyst implantation in humans, these enigmatic structures have been the subject of many studies in humans which establish their utility as important indicators of normal endocrine progression as well as indicators of uterine receptivity for blastocyst implantation [45][46][47][48][49][50]96].…”
Section: Uterodomes ('Pinopodes')-features Of the Apical Plasma Membrmentioning
confidence: 99%
See 1 more Smart Citation
“…Originally termed 'pinopods' from studies in rats which established a pinocytotic function for them in this species [43], large, rounded, smooth-surfaced projections of the apical plasma membrane have been identified in the uterine epithelium of many species during early pregnancy ranging from rabbits and rodents through camels to human beings [44,45]. Because such smooth-surfaced projections occur during the receptive phase for blastocyst implantation in humans, these enigmatic structures have been the subject of many studies in humans which establish their utility as important indicators of normal endocrine progression as well as indicators of uterine receptivity for blastocyst implantation [45][46][47][48][49][50]96].…”
Section: Uterodomes ('Pinopodes')-features Of the Apical Plasma Membrmentioning
confidence: 99%
“…Despite the undoubted utility of these structures in clinical medicine and indeed in clinical decision-making [48][49][50]96], the human 'pinopodes' do not have a significant pinocytotic function [95] and it has been suggested that the human structures be referred to as 'uterodomes' [45].…”
Section: Uterodomes ('Pinopodes')-features Of the Apical Plasma Membrmentioning
confidence: 99%
“…Later, galectin-9 was identified as a new endometrial epithelial marker for the mid-and late-secretory and decidual phases in human endometrium, in which galectin mRNA was shown to be exclusively expressed in the endometrial epithelial cells but not in stromal or immune cells [14]. Uterodomes are considered as the biological marker of uterine receptivity in vivo [15][16] and the preferred site of embryo-endometrial interactions in vitro [17]. Furthermore, uterodomes are the initial sites that contact with the floating blastocyst and play an important role in accumulation and secretion of biomolecules to the uterine cavity during the initial phase of pregnancy [18].…”
mentioning
confidence: 99%
“…103 In case of rats, in comparison, displacement of pinopod development by ormeloxifene, a selective estrogen receptor modulator, was not associated with corresponding displacement of receptivity. 92 By manipulation of follicular phase in women participating in an IVF programme, using shorter (7 days) and longer (14 days) sequential doses of exogenous estradiol followed by progesterone administration and comparison of the secretory uterine epithelium with the morphology of their normal cycles with the aid of SEM, Adams et al 83 have demonstrated that while short estradiol treatment did not alter the timed epithelial sequence apparent in an individual's natural cycle, longer estradiol treatment retarded uterodome appearance. It has also been proposed that in patients showing poor epithelial morphology in natural cycles, exogenous estradiol and progesterone supplementation might increase the abundance of pinopods, which has been correlated to improved pregnancy rates.…”
Section: Microarchitecturementioning
confidence: 98%
“…78,79 This membrane transformation and the function of these protrusions have aroused particular interest for possible use as biological markers of uterine receptivity in IVF settings. [80][81][82][83] The first observations of apical surface protrusions on uterine luminal epithelial cells were made in mice 84 and rats. 85 It was, however, Nilsson 86 who provided the first extensive discussion and illustration of apical projections, which he simply referred to as cytoplasmic protrusions and blebs with an apocrine function.…”
Section: Microarchitecturementioning
confidence: 99%